Increased self-regulation of eating behavior is associated with reduced generalized anxiety disorder in Saudi Arabia - Ghabashi, Mai Adil (Frontiers in Psychology, 2024)
There is a growing body of evidence suggesting that self-regulation of eating behavior (SREB) is closely linked to dietary habits and mental health. However, little is known about these relationships within the Saudi Arabian population. Therefore, this study aimed to cover this gap in the literature by conducting a digital cross-sectional study that used the SREB and generalized anxiety disorder (GAD-7) questionnaire, as well as a brief questionnaire about dietary habits. Linear and logistic regression analyses were used to examine such associations. In total, 651 Saudi participants were enrolled in the study. The results showed that only 15.5% demonstrated a high capacity for SREB, while 65% of the participants experienced moderate or severe symptoms of GAD. The findings indicated that greater SREB was significantly associated with reduced GAD scores (β= -0.13, 95% CI; -0.12 to -0.03; p<0.001) as well as lower BMI (β= -0.10, 95% CI; -0.08 to -0.00; p=0.01). This suggests that enhancing SREB may be a promising strategy for obesity prevention and improving mental health outcomes among the Saudi population. Interestingly, this study identified predictive factors of high capacity for SREB, including higher daily intake of fruits (OR= 2.90, 95% CI; 1.44 to 5.84; p=0.003) and regular breakfast consumption (OR= 1.64, 95% CI; 1.01 to 2.63; p=0.04). These findings underscore the importance of implementing interventions aimed at enhancing SREB, potentially by promoting healthier dietary habits, in order to support the physical and mental well-being of the Saudi population.